SUBSTITUTE TERMINOLOGY FOR 'STOCK DIVIDENDS' - Burtchett, Floyd F. (The Accounting Review, 1933)
This article focuses on stock dividends. The term stock dividend describes the form in which the dividend is declared and paid, and it implies that it is declared from surplus under the same legal limitations as any other dividend. That it is a true dividend contemplating the alienation of assets from the corporation cannot be defended upon any ground. Two terms suggest themselves, capitalization dividend and encapitalization dividend. The latter would be preferable since encapitalize carries the connotation of putting into capital. If the form of the dividend declaration were added to either of the phrases, the latter preferred, a somewhat more satisfactory terminology would be secured. In every instance the idea of locking up something in the capitalization accounts would be implied; the use of the word dividend would carry sufficient legal limitation to differentiate split-ups and recapitalizatious. It might not be necessary to add the word stock, debenture, or bond, since these would be identified by the individual declaration. Accountants can do more than any and all other persons combined to improve the unsatisfactory terminology now extant.